Evaluate consumption of electric energy of residential sector and its environmental and economic effects - Najim Abdallah Jazea; Mohammed Hussein Ali; Noora Hani Sherif (Institute of Advanced Engineering and Science, 2022)
The demand for electric power in Iraq increased significantly after 2003, The residential sector is the most consumption according to the statistics of the iraqi ministry of electricity (ICME) and the data published by the international energy agency (IEA). In this paper, a survey was applied for a sample of the population; whereby questionnaire models were used for some of the most energy consuming devices to determine the estimates of supply and demand for energy, and some data from the Iraqi Ministry of Electricity available until 2020 was relied on to predict the consumption of electrical energy for next ten years. Five Scenarios have been implemented for energy saving, CO2 gas emission and electricity production cost that reduce the accumulative energy consumed for the coming years.